Is dyslexia a form of specific language impairment? A comparison of dyslexic and language impaired children as adolescents. - Goulandris, N; Snowling, M; Walker, I (2000)
Two groups of adolescents with a childhood history of language impairment were compared with a group of developmentally dyslexic young people of the same age and nonverbal ability. The study also included two comparison groups of typically developing children, one of the same age as those in the clinical groups, and a younger comparison group of similar reading level to the dyslexic students. Tests of spoken and written language skills revealed that the adolescents with dyslexia were indistinguishable from those with resolved language impairments on spoken language tasks, and both groups performed at age-expected levels. However, both dyslexic readers and those with resolved specific language impairments showed deficits in phonological awareness. On written language tasks, a different pattern of performance was apparent. In reading and spelling, adolescents with dyslexia performed only as well as those with persistent oral language impairments and younger controls. However, their reading comprehension was better. The theoretical and educational implications of these findings are discussed.